Titanium-based alloy, titanium-based brazing filler metal and preparation method of titanium-based alloy
By adding rare earth elements to titanium-based alloys and using vacuum fast quenching process to prepare titanium-based brazing, the problem of brittle phases generated by titanium alloys during brazing is solved, and a high-strength, low-brittle and high-tough brazing joint is achieved. , broaden the application range of titanium and its alloys.
Patent Information
- Application Number
- CN202411697270.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Titanium alloys are prone to brittle phases during brazing, resulting in insufficient mechanical properties of the joints, especially at high temperatures, which limits the application range of titanium and its alloys.
By adding rare earth elements to the titanium-based alloy, a high melting point compound is formed, the oxygen content of the matrix is reduced, and the high-temperature oxidation resistance and mechanical properties of the alloy are improved. Titanium-based brazing is prepared by vacuum fast quenching process to form low-brittle and high-strength brazing joints.
It improves the tensile strength and toughness of the brazed joints, reduces brittleness, and broadens the scope of use of titanium and its alloys, so that they can be applied to occasions where the performance of the joint is high.
Smart Images

Figure CN119457574A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brazing application, and in particular to a titanium-based alloy, a titanium-based brazing filler metal and a preparation method thereof. Background Art
[0002] As an important connection method, brazing technology is widely used in aerospace, electronics, automobile manufacturing and other fields. Titanium and its alloys have been widely used in modern industry due to their excellent strength, corrosion resistance and specific strength. However, titanium alloy materials are prone to produce brittle phases during brazing, which affects the mechanical properties of the joints, especially at high temperatures, which seriously limits the application range of titanium and its alloys.
[0003] The brazing filler metal system used for traditional titanium alloy brazing is mainly composed of Ti, Zr, Cu, and Ni elements. A large amount of Zr, Al, V, Cu, and Ni elements easily generate brittle compounds during the brazing process, resulting in insufficient strength and toughness of the brazed joint. When brazing titanium alloys, brittle compound phases such as Ti3Al, Ti-V, Ti2Ni, TiNi, and TiCu will form at the interface, which will have an adverse effect on the fracture toughness and fatigue performance of the joint. Generally, the brazed specimens show brittle fracture, and the elongation after fracture is less than 5%. Although the performance of the brazed joint can be improved to a certain extent by optimizing the brazing process, due to the limitations of the brazing filler metal itself, the existing titanium-based brazing filler metals are still difficult to meet some applications with high requirements for joint performance. Summary of the invention
[0004] In view of the above situation, the present invention aims to provide a titanium-based alloy, a low-brittle titanium-based brazing filler metal and a brazing method, which are used to solve the problem of high brittleness and low strength of brazed joints using existing titanium-based brazing filler metals.
[0005] The purpose of the present invention is mainly achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a titanium-based alloy, comprising, by mass percentage, 5%-30% Zr, 10%-15% Cu, 10%-15% Ni, 0.5%-3.5% Nb, 0.1%-0.3% rare earth elements; the remainder being Ti and inevitable trace impurities.
[0007] Optionally, the rare earth element includes one or more of La, Ce and Y.
[0008] Optionally, the titanium-based alloy includes, in terms of mass percentage, Zr, 15%-25%, Cu, 12%-15%, Ni, 12%-15%, Nb, 2%-3%, rare earth elements, 0.1%-0.3%; the remainder is Ti and inevitable trace impurities.
[0009] In a second aspect, the present invention further provides a low-brittleness titanium-based brazing filler metal, comprising the above-mentioned titanium-based alloy.
[0010] Optionally, the melting point of the titanium-based solder is 820-878°C.
[0011] Optionally, the titanium-based brazing filler metal has a thickness of 0.02-0.04 mm and a width of 40-100 mm.
[0012] In a third aspect, the present invention further provides a method for preparing the above-mentioned low-brittleness titanium-based solder, comprising the following steps:
[0013] Step 1: melting the titanium-based alloy into an alloy ingot;
[0014] Step 2: Prepare the alloy ingot into titanium-based brazing filler metal through vacuum rapid quenching process.
[0015] Optionally, in step 1, the smelting temperature is 1200-1400°C.
[0016] Optionally, in step 2, a vacuum quenching process is performed in a vacuum quenching equipment.
[0017] Optionally, the vacuum quenching equipment includes a melting furnace vacuum chamber, a quenching vacuum chamber, and a vacuum silo arranged in sequence; a rotating cooling roller is provided in the quenching vacuum chamber, and the rotating cooling roller has a spindle-shaped internal space, and a cooling medium flows through the spindle-shaped internal space.
[0018] Optionally, a turntable tundish system, a strip guiding cooling roller and a strip anti-accumulation track are also provided in the rapid quenching vacuum chamber, and the rotating cooling roller, the turntable tundish system, the strip guiding cooling roller and the strip anti-accumulation track are arranged in sequence.
[0019] Optionally, a smelting device is provided in the vacuum chamber of the melting furnace, and a smelting crucible is provided in the smelting device.
[0020] Optionally, the smelting device is a medium frequency melting furnace.
[0021] Optionally, the turntable tundish system includes a plurality of rotatable tundishes, and the rotating cooling roller is arranged below the tundishes.
[0022] Optionally, a nozzle is provided below the tundish to spray cooling medium toward the rotating cooling roller.
[0023] Optionally, the number of the intermediate packages is 3-5.
[0024] Optionally, the capacity of the tundish is 25-100 kg.
[0025] Optionally, an online instant grinding device is also included, and the online instant grinding device is arranged toward the working surface of the rotating cooling roller.
[0026] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0027] a) The present invention adds rare earth elements to titanium-based alloys, forms high-melting-point compounds through internal oxidation of rare earth elements, reduces the oxygen content of the matrix, and improves the high-temperature oxidation resistance and mechanical properties of the alloy. Rare earth elements enhance the mechanical properties of titanium alloys in the form of solid solution and intermetallic compounds. The introduction of rare earth elements provides an effective way to optimize the performance of titanium-based brazing fillers, while improving the strength of the brazed joint (the tensile strength of the brazed joint is 930-950MPa) and toughness, while reducing the brittleness of the brazed joint (the elongation after fracture is 11%-15%, which is much higher than the elongation after fracture of the prior art <5%), broadening the scope of use of titanium and its alloys, so that they can be used in occasions with high joint performance requirements.
[0028] b) The present invention selects La, Ce and Y as rare earth elements, which facilitates the solid solution of the rare earth elements in other elements in the titanium-based alloy and is more likely to form intermetallic compounds, thereby ensuring the enhancement of the mechanical properties of the titanium-based alloy. In addition, since the prices of La, Ce and Y are lower than those of other rare earth elements, it is beneficial to reduce production costs.
[0029] c) The preparation method of the solder of the present invention adopts a vacuum quenching device with strong cooling intensity and uniform cooling, and the yield rate of preparing titanium-based alloy into titanium-based solder (amorphous strip) is increased from about 50% to more than 80%.
[0030] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0032] Figure 1 The morphology of the amorphous solder strip obtained in Example 1;
[0033] Figure 2 The tensile test specimen fracture diagram of the brazed joint of Example 1 subjected to a tensile strength test;
[0034] Figure 3 The tensile stress-strain curve of the brazed joint of Example 1 subjected to a tensile strength test;
[0035] Figure 4 This is the typical structure of the brazed joint of Example 1;
[0036] Figure 5 The morphology of the amorphous solder strip obtained in Example 2;
[0037] Figure 6 The tensile test specimen fracture diagram of the brazed joint of Example 2 subjected to a tensile strength test;
[0038] Figure 7 The tensile stress-strain curve of the brazed joint of Example 2 subjected to a tensile strength test;
[0039] Figure 8 This is the typical structure of the brazed joint of Example 2;
[0040] Fig. 9 The morphology of the amorphous solder strip obtained in Example 3;
[0041] Fig.10 The tensile test specimen fracture diagram of the brazed joint of Example 3 subjected to a tensile strength test;
[0042] Fig.11 The tensile stress-strain curve of the brazed joint of Example 3 subjected to a tensile strength test;
[0043] Fig.12 This is the typical structure of the brazed joint of Example 3;
[0044] Fig.13 This is a schematic diagram of the structure of the rotating cooling roller of the present invention;
[0045] Figure 14-1 This is a flow field velocity cloud diagram (longitudinal section) of the rotating cooling roller core barrel of the present invention;
[0046] Figure 14-2 This is a flow field velocity cloud diagram (longitudinal section) of the rotating cooling roller core barrel of the present invention;
[0047] Figure 15-1 It is the velocity vector diagram of the flow field of the rotating cooling roller core barrel of the present invention (longitudinal section);
[0048] Figure 15-2 It is the velocity vector diagram of the flow field of the rotating cooling roller core barrel of the present invention (longitudinal section);
[0049] Fig.16 It is a schematic diagram of the structure of the vacuum rapid quenching equipment of the present invention.
[0050] Reference numerals:
[0051] 1-rotating shaft; 2-flange; 3-cooling copper sleeve; 4-core barrel; 5-rotating dynamic seal; 6-rolling bearing; D-spiral groove width; h-spiral groove height; 7-melting furnace vacuum chamber; 8-smelting device; 9-quick quenching vacuum chamber; 10-vacuum silo; 11-online instant grinding device; 12-rotating cooling roller; 13-turntable tundish system; 14-strip guide cooling roller; 15-strip anti-stacking track. DETAILED DESCRIPTION
[0052] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0053] In a first aspect, the present invention provides a titanium-based alloy, wherein the components of the titanium-based alloy, in terms of mass percentage, include: Zr, 5%-30%, Cu, 10%-15%, Ni, 10%-15%, Nb, 0.5%-3.5%, rare earth elements, 0.1%-0.3%; the remainder is Ti and unavoidable trace impurities.
[0054] Specifically, the rare earth element of the present invention is one or more of La, Ce and Y.
[0055] The following is a detailed description of the effects and dosage of the components in the present invention:
[0056] Zr: The addition of Zr element can improve the fluidity of the solder and the wettability during the soldering process, thereby facilitating the formation of a uniform soldering joint. Therefore, the present invention limits the Zr content to 5%-30%.
[0057] Cu: Cu element plays a role in lowering the melting point and increasing fluidity in the solder, which helps the solder to better fill the joint gap and is also beneficial to the diffusion of elements and phase change. Therefore, the present invention limits the Cu content to 10% to 15%.
[0058] Ni: The addition of Ni element can further improve the corrosion resistance and mechanical properties of the solder, and enhance the durability and service life of the brazing joint. Therefore, the present invention limits the Ni content to 10% to 15%.
[0059] Nb: The addition of an appropriate amount of Nb element can effectively improve the mechanical properties and corrosion resistance of the amorphous alloy, while excessive Nb element may lead to a decrease in performance. Therefore, the present invention limits the Nb content to 0.5% to 3.5%.
[0060] Rare earth elements: Rare earth elements can be internally oxidized to form high melting point compounds, reduce the oxygen content of the matrix, and improve the high temperature oxidation resistance and mechanical properties of the alloy. In the present invention, the rare earth elements enhance the mechanical properties of the titanium alloy in the form of solid solution and intermetallic compounds. Therefore, the present invention limits the rare earth element content to 0.1% to 0.3%.
[0061] Ti: Ti element is the remainder, and its content is greater than 50%, ensuring that the solder composition is titanium-based.
[0062] The titanium-based alloy is prepared by the following method: weighing each component according to the above ratio, -1 Pa, smelting at a temperature of 1200-1400°C and keeping warm for 10-25 minutes.
[0063] In a second aspect, the present invention further provides a low-brittleness titanium-based brazing filler metal, comprising the above-mentioned titanium-based alloy.
[0064] In order to further improve the comprehensive properties of the above-mentioned low brittleness titanium-based solder, the components of the above-mentioned titanium-based alloy can be calculated by mass percentage: Zr, 15%-25%, Cu, 12%-15%, Ni, 12%-15%, Nb, 2%-3%, rare earth elements, 0.1%-0.3%, and the balance is Ti and inevitable trace impurities.
[0065] Specifically, the microstructure of the low-brittle titanium-based solder includes: Cu and Ni elements diffuse rapidly into the matrix at the brazing interface, Ti element diffuses rapidly into the solder, and a diffusion layer is first formed near the matrix on both sides, and gradually widens with the increase of brazing temperature and holding time, and then β-Ti nucleates and grows in the liquid solder. At this time, the remaining liquid phase mainly contains Ti, Zr, Cu, and Ni elements, and solidifies to form (Ti, Zr) 2 (Cu, Ni) phase. As the temperature decreases, high-temperature β-Ti gradually undergoes eutectoid decomposition to generate α-Ti distributed in lamellar form. The addition of rare earth elements and Nb elements is conducive to the precipitation of lamellar α-Ti, reducing the volume content of the brittle (Ti, Zr) 2 (Cu, Ni) phase, thereby increasing the toughness of the joint.
[0066] The design concept of the low-brittle titanium-based brazing filler metal of the present invention is as follows: the present invention adds rare earth elements to the titanium-based alloy, forms high-melting-point compounds through internal oxidation of the rare earth elements, reduces the matrix oxygen content, and improves the high-temperature oxidation resistance and mechanical properties of the alloy. Rare earth elements enhance the mechanical properties of titanium alloys in the form of solid solution and intermetallic compounds, while improving the strength of the brazed joint (the tensile strength of the brazed joint is 930-950MPa) and toughness, while reducing the brittleness of the brazed joint (the elongation after fracture is 11%-15%, which is much higher than the elongation after fracture of the prior art <5%), broadening the scope of use of titanium and its alloys, so that it can be used in occasions with high requirements for joint performance.
[0067] In a third aspect, the present invention further provides a method for preparing a low-brittle titanium-based brazing filler metal, comprising the following steps:
[0068] Step 1: melting the titanium-based alloy into an alloy ingot;
[0069] Step 2: Prepare the alloy ingot into an amorphous strip, i.e., titanium-based brazing filler metal, through a vacuum rapid quenching process.
[0070] Specifically, in step 1, the smelting temperature is 1200-1400°C, for example, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C.
[0071] The holding time is 10-25 minutes, for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes.
[0072] Vacuum degree<10 -1 Pa, for example, 1×10 -2 Pa, 3×10 -2 Pa, 5×10 -2 Pa, 7×10 -2 Pa, 9×10 -2 Pa.
[0073] Specifically, in step 2, in the vacuum rapid quenching process, the melting temperature is: 1100-1400°C, for example, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C.
[0074] Vacuum degree ≤10 -2 Pa, for example, 1×10 -2 Pa, 1×10 -3 Pa, 5×10 -3 Pa, 7×10 -3 Pa, 9×10 -3 Pa.
[0075] In step 2, a vacuum quenching process is performed in a vacuum quenching device. Fig.16 As shown, the vacuum quenching equipment includes a melting furnace vacuum chamber 7, a quenching vacuum chamber 9, and a vacuum silo 10 which are arranged in sequence; the melting furnace vacuum chamber 7, the quenching vacuum chamber 9, and the vacuum silo are independent closed structures, and can be connected to the atmospheric environment without affecting each other and perform corresponding operations respectively.
[0076] A smelting device 8 is provided in the vacuum chamber 7 of the melting furnace, and a smelting crucible for placing the master alloy is provided in the smelting device 8 .
[0077] The quick quenching vacuum chamber 9 is provided with a rotating cooling roller 12, a turntable tundish system 13, a strip guiding cooling roller 14 and a strip anti-stacking track 15 in sequence.
[0078] In a specific embodiment, the smelting device 8 is a medium frequency melting furnace. The capacity of the medium frequency melting furnace is 10-300 kg, preferably 50-150 kg.
[0079] The turntable tundish system 13 is provided with 3-5 rotatable independent tundishes, each of which can be driven by a horizontal disc to rotate and / or stop along the circumference of the disc. The rotating cooling roller 12 is arranged below the tundish, and a nozzle is arranged below each tundish to spray cooling medium to the rotating cooling roller 12. Exemplarily, the capacity of the tundish is 25-100 kg.
[0080] In a preferred embodiment, the vacuum quenching equipment also includes an online instant grinding device 11, which is arranged toward the working surface of the rotating cooling roller 12 and can trim and polish the surface of the rotating cooling roller 12 when the smelting device 8 is feeding and melting.
[0081] The strip guide cooling roller 14 is a two-roller adjustable slit structure, which is arranged at the exit end of the strip leaving the rotating cooling roller 12, controls the flight state of the strip after leaving the roller, guides the strip through the slit into the strip anti-stacking track 15, and performs secondary cooling on the strip.
[0082] like Fig.13 As shown, the rotating cooling roller includes a rotating shaft 1, a flange 2, a cooling jacket 3, a core barrel 4, a rotating dynamic seal 5 and a rolling bearing 6.
[0083] The flange 2, the core barrel 4 and the cooling jacket 3 form an internal flow path through which the cooling medium flows. Fig.13 The arrow in the middle indicates the flow direction of the cooling medium.
[0084] The cooling jacket 3 is a hollow cylinder without end faces. The two ends of the cooling jacket are respectively connected to a flange 2, and the other ends of the two flanges 2 are respectively connected to the rotating shaft 1. The two flanges 2 and the cooling jacket 3 form a spindle-shaped internal space. The core barrel 4 is arranged in the internal space formed by the flange 2 and the cooling jacket 3, and a gap is left between the flange 2 and the cooling jacket 3 for the cooling medium to flow through. Specifically, as Fig.13 As shown, the longitudinal section of the structure formed by the flange 2 and the cooling jacket 3 is similar to a hexagon.
[0085] The flange 2 has a conical structure with a conical angle of 40°-70°, for example, 40°, 50°, 60°, 70°. The inner wall of the flange 2 is provided with a guide groove, which enables the cooling medium (for example, water) to be quickly distributed after entering the cooling roller.
[0086] Specifically, the end of the flange 2 with a larger diameter is connected to the cooling jacket 3 , and the end of the flange 2 with a smaller diameter is connected to the rotating shaft 1 .
[0087] The core barrel 4 has a spindle-shaped sealed cavity structure, and its shape corresponds to the spindle-shaped internal space. Both ends of the core barrel 4 are respectively connected to the rotating shaft 1. A rolling bearing 6 is fixedly connected to the connection between the core barrel 4 and the rotating shaft 1, which can keep the core barrel 4 in a follow-up state (water flow) when the rotating shaft 1 and the cooling jacket 3 rotate.
[0088] The flange 2, the core barrel 4 and the cooling jacket 3 form an internal flow path with a spindle-shaped streamlined structure. The streamlined structural design is conducive to overcoming the centrifugal force, and can reduce the influence of the centrifugal force of the high-speed rotation of the cooling roller on the cooling medium, especially the cooling medium in the annular water path between the cooling jacket and the core barrel, thereby facilitating the rapid distribution of the cooling medium through the inlet and the rapid collection of the cooling medium through the internal flow path to the outlet, thereby improving the cooling intensity.
[0089] In a preferred embodiment, the longitudinal section of the core barrel 4 is similar to a hexagon.
[0090] In another embodiment, the rotary cooling roller further includes a locking member (e.g., a buckle) to fix the core barrel 4 to the rotating shaft 1, and the core barrel 4 is in a rotating state, that is, the core barrel 4 rotates with the rotating shaft 1. The present invention can realize the switching of the core barrel 4 in the following state and the rotating state by setting the locking member, and the cooling intensity of the core barrel 4 in the following state and the rotating state is different (see Table 1), thereby realizing the adjustment of the cooling intensity and expanding the application range of the rotary cooling roller of the present invention.
[0091] Specifically, the interior of the rotating shaft 1 is hollow for the cooling medium to flow through. The rotating shaft 1 includes two sections, one for the inflow of the cooling medium and the other for the outflow of the cooling medium. Each section of the rotating shaft is connected to the end with a smaller diameter of the flange 2. The rotating shaft 1 is open at one end and closed at the other end. A through hole connected to the outside is provided on the side wall of each section of the rotating shaft. The through hole is provided at the gap left between the flange 2 and the core barrel 4 to enable the cooling medium to flow in or out of the rotating shaft and the internal flow path, that is, to enable the cooling medium in the rotating shaft 1 to flow into the internal flow path or to enable the cooling medium in the internal flow path to flow into the rotating shaft 1, so that the cooling medium is collected at the outlet and flows out after flowing through the internal flow path.
[0092] Specifically, there are multiple through holes, and the multiple through holes are evenly distributed along the circumference of the rotating shaft 1 .
[0093] In a preferred embodiment, a rotary dynamic seal 5 is further provided at the connection between the core barrel and the rotating shaft to prevent the cooling medium in the internal flow path from flowing into the cavity of the core barrel 4 .
[0094] It should be noted that, compared with a solid structure, the core barrel 4 designed as a hollow structure is beneficial to reducing the weight of the cooling roller, saving raw materials and reducing costs.
[0095] The inner wall of the cooling jacket 3 is provided with a single or multiple spiral grooves to form a spiral water channel. Preferably, it is a multiple spiral groove, for example, 3-5 mutually parallel spiral grooves. When in use, the present invention increases the cooling capacity of the system by controlling the flow direction of the cooling medium to be opposite to the rotation direction of the cooling roller.
[0096] Specifically, the pitch S of the spiral groove is 50-100mm. The cross section of the spiral groove is semi-elliptical, semi-circular, triangular, rectangular or trapezoidal. When the cross section of the spiral groove is semi-elliptical or rectangular, the ratio of width to height is 2-3.5. The present invention can reduce the relatively static area (dead zone) between the cooling medium and the inner surface of the cooling roller formed by high-speed rotation when the cooling medium flows in the spiral waterway by arranging the spiral groove on the inner wall of the cooling sleeve 3; and the existence of the dead zone causes the cooling medium water to contact and vaporize on the inner surface of the cooling roller to form an air film, which hinders heat transfer and is prone to danger in severe cases (excessive steam pressure). The present invention can improve the cooling intensity on the one hand and improve production safety on the other hand by arranging the spiral groove on the inner wall of the cooling sleeve 3.
[0097] The cooling jacket 3 is made of copper, copper alloy or other materials with high thermal conductivity. The gap between the cooling jacket 3 and the core barrel 4 is 5-10 mm on one side, for example, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm. The gap between the flange 2 and the core barrel 4 is 30-40 mm on one side, for example, 30 mm, 32 mm, 35 mm, 37 mm, 39 mm, 40 mm.
[0098] Compared with the prior art, the rotary cooling roller of the present invention has the following beneficial technical effects:
[0099] 1) The flange of the present invention has a conical structure, which forms a spindle-shaped internal space after being connected to a cooling jacket without end faces and having a hollow interior. The core barrel is a spindle-shaped sealed cavity structure, which corresponds to the spindle-shaped internal space formed by the flange and the cooling roller, and has a gap between the flange and the cooling jacket, respectively, so as to construct an internal flow path of a spindle-shaped streamlined structure. The streamlined structural design is conducive to overcoming the centrifugal force, and can reduce the influence of the centrifugal force of the high-speed rotation of the cooling roller on the poor internal flow of the cooling medium, especially the cooling medium in the annular water path between the cooling jacket and the core barrel, thereby facilitating the rapid distribution of the cooling medium through the inlet, and the rapid collection of the cooling medium through the internal flow path to the outlet to flow out, ensuring that the cooling medium can pass quickly. On the one hand, it can take away more heat in a short time, achieving the purpose of efficient heat exchange, thereby improving the cooling intensity; on the other hand, it can increase the cooling uniformity and increase the yield rate of amorphous strip to more than 80% (the yield rate of amorphous strip in the prior art is about 50%).
[0100] 2) The present invention connects a rolling bearing at the connecting end of the core barrel and the rotating shaft, so that the core barrel can be in a follow-up state when the rotating shaft and the cooling sleeve rotate, which is equivalent to applying a shear force perpendicular to the direction of the centrifugal force to the internal cooling medium, with the purpose of offsetting part of the centrifugal force, increasing the axial movement efficiency of the cooling medium, and improving the cooling intensity of the rotating cooling roller.
[0101] 3) The present invention fixes the core barrel to the rotating shaft by setting a locking member, so that the core barrel is in a rotating state, that is, the core barrel rotates with the rotating shaft. The cooling intensity of the core barrel in the following state and the rotating state is different (see Table 1), thereby achieving the adjustment of the cooling intensity and expanding the application range of the rotating cooling roller of the present invention.
[0102] 4) The present invention can achieve rapid distribution of the cooling medium by arranging the guide groove on the inner wall of the flange, ensuring that the cooling medium can pass quickly, taking away more heat in a short time, achieving the purpose of efficient heat exchange, and further improving the cooling intensity.
[0103] 5) The present invention provides single-channel or multi-channel spiral grooves on the inner wall of the cooling jacket, and increases the cooling capacity of the system by controlling the flow direction of the cooling medium to be opposite to the rotation direction of the cooling roller, thereby improving the cooling intensity.
[0104] 6) The cooling roller of the present invention has great promotion and practical value. It is applied to vacuum quenching equipment and can prepare alloy system amorphous foil strips that are urgently needed in the aerospace field and do not have strong amorphous forming ability. After being widely promoted and applied, it will produce good economic and social benefits.
[0105] 7) The rotating cooling roller in the vacuum quenching equipment of the present invention constructs an internal flow path with a spindle-shaped streamline structure, which is conducive to overcoming the centrifugal force and can reduce the influence of the centrifugal force of the high-speed rotation of the cooling roller on the poor internal flow of the cooling medium, especially the cooling medium in the annular water path between the cooling jacket and the core barrel, thereby facilitating the rapid distribution of the cooling medium through the inlet and the rapid convergence to the outlet through the internal flow path to flow out, thereby ensuring that the cooling medium can pass quickly. On the one hand, more heat can be taken away in a short time, achieving the purpose of efficient heat exchange, thereby improving the cooling intensity; on the other hand, it can increase the cooling uniformity and increase the yield rate of amorphous strip to more than 80% (the yield rate of amorphous strip in the prior art is about 50%).
[0106] The thickness of the amorphous strip prepared by the method of the present invention is 0.02-0.04 mm, for example, 0.02 mm, 0.03 mm, 0.04 mm. The width of the amorphous strip is 40-100 mm, for example, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm.
[0107] In addition, the melting point of the titanium-based brazing filler metal prepared by the above preparation method is 820-878°C, for example, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 878°C.
[0108] In a fourth aspect, the present invention further provides a method for brazing using the above-mentioned titanium-based brazing filler metal, comprising the following steps:
[0109] Step a: placing a titanium-based brazing filler metal on the surface of the component to be welded and fixing and clamping it with a fixture;
[0110] Step b: placing the component to be welded with the titanium-based brazing filler metal fixed thereon in a vacuum brazing furnace, brazing, and heat preservation.
[0111] Specifically, in step a, the material of the component to be welded is TA15 titanium alloy.
[0112] Specifically, in step b, the brazing temperature is 890-980°C, for example, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, preferably 900-950°C. The holding time is 5-60min, for example, 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min, preferably 15-25min. The vacuum degree during brazing is ≤1×10 -2 Pa, for example, 1×10 -2 Pa, 5×10 -3 Pa, 7×10 -3Pa, 9×10 -3 Pa.
[0113] The present invention can achieve both strong and tough properties of the connection interface by controlling the brazing temperature to 890-980° C. and the heat preservation time to 5-60 min, thereby obtaining low brittleness and high-strength brazing quality.
[0114] Examples 1-6
[0115] The advantages of precise control of the composition and process parameters of the low-brittleness titanium-based solder of the present invention are demonstrated below with specific examples and comparative examples.
[0116] Examples 1-6 of the present invention provide a low-brittle titanium-based brazing filler metal and a preparation method and a brazing method thereof. The chemical compositions of the brazing fillers of Examples 1-6 are shown in Table 1.
[0117] The preparation method and brazing method of the solder of Examples 1-6 include: smelting into alloy ingots, preparing the alloy ingots into titanium-based solder (amorphous strip) using a vacuum rapid quenching process, fixing the solder, brazing, and heat preservation.
[0118] It should be noted that the equipment used in the vacuum quenching process of Examples 1-6 is a vacuum quenching equipment, and the rotating cooling roller in the vacuum quenching equipment is the cooling roller of Example 7.
[0119] The specific process parameters of Examples 1-6 are shown in Table 2. The tensile strength of the brazed joints was tested, and the test results are shown in Table 3.
[0120] Table 1 Chemical composition, wt%
[0121] Example Zr Cu Ni Nb La Ce Y Ti 1 30 15 10 0.5 0.2 0 0 margin 2 20 10 15 1 0 0.1 0 margin 3 20 15 10 3 0 0.2 0.1 margin 4 5 10 15 3.5 0.1 0 0 margin 5 25 15 15 2 0 0.3 0 margin 6 15 12 12 1.5 0 0.1 0.2 margin
[0122] Table 2 Production process parameters
[0123]
[0124] Table 3 Partial performance test results
[0125]
[0126] Figure 1 , Figure 5 and Fig. 9 The morphologies of the amorphous solder strips obtained in Example 1, Example 2 and Example 3 are shown respectively. Figure 1 , Figure 5 and Fig. 9 It can be seen that the strips of the three components have good strip forming properties, are continuous and have no holes.
[0127] Figure 2 , Figure 6 and Fig.10The tensile test specimens of the brazed joints of Example 1, Example 2 and Example 3 are respectively subjected to tensile strength tests. Figure 2 , Figure 6 and Fig.10 It can be seen that when the three kinds of solder strips are used for brazing of titanium alloy, the corresponding brazed joints are all broken at the matrix after stretching at room temperature, indicating that the brazing performance is stronger than that of the matrix.
[0128] Figure 3 (3 samples of each component), Figure 7 (3 samples of each ingredient) and Fig.11 (3 samples for each component) are respectively the tensile stress-strain curves of the brazed joints of Example 1, Example 2 and Example 3 for tensile strength test, and the average tensile strength is shown in Table 3. As can be seen from Table 3, after brazing with the brazing filler metal of the present invention, the tensile strength of the brazed joint is greater than 930 MPa, and the elongation after fracture is greater than 11%. While improving the strength and toughness of the brazed joint, the brittleness of the brazed joint is reduced, and the application range of titanium and its alloys is broadened, so that it can be applied to occasions with higher joint performance requirements.
[0129] Figure 4 , Figure 8 and Fig.12 The typical structures of the brazed joints of Example 1, Example 2 and Example 3 are shown respectively. Figure 4 , Figure 8 and Fig.12 It can be seen that the typical structure of the brazed joint is lamellar structure. The proportion of lamellar structure is shown in Table 4 below.
[0130] Table 4 Microstructure of solder
[0131] serial number Microstructure Organization proportion Example 1 Lamellar tissue 75% Example 2 Lamellar tissue 78% Example 3 Lamellar tissue 90%
[0132] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor performance as comparative examples.
[0133] Comparative Example 1
[0134] This comparative example provides a titanium-based solder, the components of which are similar to those of Example 2, except that no rare earth elements are added. The specific components are shown in Table 5 below. The preparation method is the same as that of Example 1, which will not be repeated here.
[0135] Comparative Example 2
[0136] This comparative example provides a titanium-based solder, whose components are similar to those of Example 2, except that the content of rare earth elements is 0.5% (not within the range of 0.1%-0.3%). The specific components are shown in Table 5 below. The preparation method is the same as that of Example 1 and will not be repeated here.
[0137] Comparative Example 3
[0138] This comparative example provides a titanium-based solder, the components of which are the same as those of Example 2, except that the melting temperature in step 1 of the preparation method is 1000° C. (see Table 6).
[0139] The main performance test results of the comparative titanium-based solder are shown in Table 7.
[0140] Table 5 Chemical composition, wt%
[0141] Comparative Example Zr Cu Ni Nb La Ce Y Ti 1 20 10 15 1 0 0 0 margin 2 20 10 15 1 0.5 0 0 margin 3 20 10 15 1 0 0.1 0 margin
[0142] Table 6 Production process parameters
[0143]
[0144] Table 7 Partial performance test results
[0145]
[0146] By comparing the data in Table 3 and Table 7, it can be seen that when no rare earth element is added to the brazing material, or too much rare earth element is added and the content is not within the range of 0.1%-0.3%, the strength of the brazed joint after brazing is only 860-870MPa (much lower than the greater than 930MPa of the present invention), and the elongation after fracture of the fracture is only 4.6-5.2% (much lower than the greater than 11% of the present invention). It is shown that too much or too little content of rare earth elements will reduce the strength and toughness of the brazed joint after brazing. It is proved that the present invention can improve the strength of the brazed joint (tensile strength of the brazed joint is 930-950MPa) and toughness while reducing the brittleness of the brazed joint (elongation after fracture is 11%-15%, much higher than the elongation after fracture of the prior art <5%) by adding rare earth elements and controlling the content of rare earth elements to 0.1%-0.3%, thereby broadening the scope of use of titanium and its alloys, so that it can be applied to occasions with high requirements for joint performance.
[0147] In addition, by comparing the data in Table 3 and Table 7, it can be seen that when the melting temperature is too low (not within the range of 1200-1400°C), the tensile strength of the brazed joint is only 870MPa (much lower than the greater than 930MPa of the present invention), and the elongation after fracture is only 6.1% (much lower than the greater than 11% of the present invention). This proves that the melting temperature also has a great influence on the strength and toughness of the brazed joint. Controlling the melting temperature to 1200-1400°C can improve the strength of the brazed joint (the tensile strength of the brazed joint is 930-950MPa) and toughness, while reducing the brittleness of the brazed joint (the elongation after fracture is 11%-15%, which is much higher than the elongation after fracture of the prior art <5%), broadening the scope of use of titanium and its alloys, so that it can be used in occasions with high requirements for joint performance.
[0148] In addition, it can be seen from Table 4 that the typical structure of the brazed joint obtained by using the titanium-based brazing filler metal, preparation method and brazing method of the present invention is a lamellar structure, and the lamellar structure accounts for as high as 75%-90%, thereby making the brazed joint excellent in strength and toughness.
[0149] Example 7 (spindle-shaped cooling roller, core barrel following motion)
[0150] This embodiment uses a rotating cooling roller with a shaft diameter of 100mm, a cooling sleeve made of copper, an outer diameter of 380mm, an outer diameter of a core barrel of 304mm, and four parallel spiral grooves on the inner wall of the copper sleeve. The aspect ratio D / h of the spiral grooves is 2.5, and the pitch S is 80mm.
[0151] Example 8 (spindle-shaped cooling roller, core barrel rotation)
[0152] This embodiment is basically the same as the embodiment 7, except that it also includes a locking member (clip) for fixing the core barrel 4 to the rotating shaft 1 so that the core barrel is in a rotating state.
[0153] Comparative Example 4 (Right-angle cooling roller, rotating core barrel)
[0154] Compared with Example 7, the structure of the rotating cooling roller is the structure involved in the patent with patent number ZL201621099453.5.
[0155] Under the same simulation conditions, the velocity field and temperature field of the rotating cooling roller during cooling of Example 7, Example 8 and Comparative Example 4 were analyzed by finite element simulation. The results are as follows: Figure 14-1 , Figure 14-2 , Figure 15-1 and Figure 15-2 The simulation data are shown in Table 8.
[0156] Table 8 Simulation data analysis table
[0157]
[0158]
[0159] It can be seen from the data in Table 8 that the water outlet speed of the spindle-shaped cooling roller (Example 7 and Example 8) of the present invention is significantly greater than the water outlet speed of the right-angle cooling roller (Comparative Example 4). After the cooling medium passes through the spindle-shaped copper roller, the outlet speed is faster, indicating that the cooling medium can take away more heat in a short time, so that the water outlet temperature of the spindle-shaped cooling roller (Example 7 and Example 8) is significantly higher than the water outlet temperature of the right-angle cooling roller (Comparative Example 4), proving that the cooling intensity of the spindle-shaped cooling roller is significantly greater than the cooling intensity of the right-angle cooling roller.
[0160] Furthermore, by comparing the data of Example 7 and Example 8 in Table 8, it is found that compared with the core barrel rotation (Example 8), the core barrel follower (Example 7) has a faster water outlet speed, and the cooling medium between the cooling jacket and the core barrel has a smaller speed along the tangential direction. The smaller the speed of the cooling medium between the cooling jacket and the core barrel along the tangential direction, the smaller the effect of the centrifugal force. It can be seen that compared with the core barrel rotation (Example 8), the core barrel follower (Example 7) can further reduce the influence of the centrifugal force, improve the axial passing capacity of the cooling medium, further improve the cooling efficiency, and then improve the cooling intensity.
[0161] In addition, by Figure 14-1 It can be seen that when the core barrel rotates, the cooling water flow rate is faster (the cloud is red), but Figure 15-1 It can be further known that the fast speed is because its tangential speed is large, that is, it is greatly affected by the centrifugal force, which ultimately causes the outlet speed to be slow.
[0162] Example 9
[0163] This embodiment is basically the same as Embodiment 1, except that the rotating cooling roller in the vacuum quenching equipment is the cooling roller of Embodiment 8.
[0164] Comparative Example 5
[0165] This comparative example is substantially the same as Example 1, except that the rotating cooling roller in the vacuum quenching apparatus is the cooling roller of Comparative Example 4.
[0166] The yield rates of titanium-based solders (amorphous strips) of Examples 1-6, Example 9 and Comparative Example 5 are shown in Table 9.
[0167] Table 9 Yield of amorphous strip
[0168] serial number Yield / % Example 1 85 Example 2 87 Example 3 88 Example 4 87 Example 5 90 Example 6 86 Example 9 81 Comparative Example 5 48
[0169] It can be seen from Table 9 that the vacuum quenching equipment composed of a spindle-shaped rotating cooling roller in the vacuum quenching process has a yield rate of more than 80% (specifically 81%-90%) for amorphous strips, while the vacuum quenching equipment composed of a right-angle rotating cooling roller has a yield rate of 48% for amorphous strips. It can be seen that the vacuum quenching equipment with strong cooling intensity and uniform cooling is used in the preparation method of the solder of the present invention, and the yield rate of preparing titanium-based alloy into titanium-based solder (amorphous strip) is increased from about 50% to more than 80%.
[0170] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A titanium-based alloy, characterized in that: Calculated by mass percentage, it includes: Zr, 5%-30%, Cu, 10%-15%, Ni, 10%-15%, Nb, 0.5%-3.5%, rare earth elements, 0.1%-0.3%; the balance is Ti and inevitable trace impurities.
2. The titanium-based alloy according to claim 1, characterized in that The rare earth element includes one or more of La, Ce and Y.
3. The titanium-based alloy according to claim 1, characterized in that Calculated by mass percentage, the titanium-based alloy includes: Zr, 15%-25%, Cu, 12%-15%, Ni, 12%-15%, Nb, 2%-3%, rare earth elements, 0.1%-0.3%; the remainder is Ti and inevitable trace impurities.
4. A titanium-based brazing filler metal, characterized in that: The titanium-based alloy comprises the titanium-based alloy according to any one of claims 1 to 3.
5. The titanium-based brazing filler metal according to claim 4, characterized in that: The melting point of the titanium-based solder is 820-878°C.
6. The titanium-based brazing filler metal according to claim 4, characterized in that: The titanium-based solder has a thickness of 0.02-0.04 mm and a width of 40-100 mm.
7. A method for preparing the titanium-based brazing filler metal according to any one of claims 4 to 6, characterized in that: The steps include: Step 1: Melting the titanium-based alloy according to any one of claims 1 to 3 into an alloy ingot; Step 2: Prepare the alloy ingot into titanium-based brazing filler metal through vacuum rapid quenching process.
8. The preparation method according to claim 7, characterized in that: In step 1, the smelting temperature is 1200-1400°C.
9. The preparation method according to claim 7, characterized in that: In step 2, a vacuum quenching process is performed in a vacuum quenching device.
10. The preparation method according to claim 9, characterized in that: The vacuum rapid quenching equipment comprises a melting furnace vacuum chamber, a rapid quenching vacuum chamber, and a vacuum silo which are arranged in sequence; a rotating cooling roller is arranged in the rapid quenching vacuum chamber.
Citation Information
Patent Citations
Rotatory chill roll of fast quenching with strong heat transfer ability
CN206263228U
Belt-shaped brazing material for medium and low temperature brazing of titanium alloy, and preparation method and brazing method thereof
CN110666396A
ZrTiNiNbHf brazing filler metal and brazing method
CN112453759A
600 DEG C / 1 GPa-grade high-temperature ultrahigh-strength titanium alloy and preparation method thereof
CN115386768A
Amorphous titanium-based brazing filler metal strip and preparation method and application thereof
CN115971723A